Modeling and simulation of software architecture in discrete event system specification for quality evaluation. (March 2014) - Bogado, Verónica; Gonnet, Silvio; Leone, Horacio
Software quality is an important issue in software engineering. The evaluation of software architecture is crucial to achieve quality scenarios, which reduces development and maintenance costs. This work presents a discrete event simulation environment for the software architecture assessment considering both functional and quality aspects. Discrete event system specification (DEVS) formalism and the underlying framework are used to specify the simulation elements. DEVS is based on the system theory and follows the engineering and object-oriented fundamentals to construct complex dynamic systems. The proposed environment is built in a modular and hierarchical way that provides scalability and reusability advantages. Although the proposal is focused on three quality attributes and a few metrics, this approach enables the definition of new elements and metrics related to other quality attributes that can be visible at runtime. A traditional architecture illustrates the proposal, where preliminary computational experiments for this real software system and concrete quality scenarios demonstrate the feasibility of the integrated simulation environment for the software architecture evaluation. In addition, a discussion shows how the results could help architects make design decisions to improve software quality during development.